Electronic influences of bridging and chelating diimine ligand coordination in formamidinate-bridged Rh2(II, II) dimers. (8th January 2016) - White, Travis A.; Dunbar, Kim R.; Thummel, Randolph P.; Turro, Claudia
Graphical abstract: The variation of the coordinated diimine ligand between bridging and bidentate chelating modes impacts the light absorbing and electronic properties of formamidinate-bridged Rh2 II, II complexes. The two new complexes exhibit broad, strong absorption throughout the UV–visible range which can be useful for the efficient absorption of solar energy. Abstract: Two new formamidinate-bridged Rh2 II, II complexes, cis -[Rh2 II, II (μ-DTolF)2 (μ-np)2 ] 2+ (3 ; DTolF =  N, N ′ -di-p -tolylformamidinate; np = 1, 8-naphthyridine) and cis -[Rh2 II, II (μ-DTolF)2 (κ 2 -dap)2 ] 2+ (4 ; dap = 1, 12-diazaperylene), were synthesized from cis -[Rh2 II, II (μ-DTolF)2 (CH3 CN)6 ](BF4 )2 (1 ), and their properties were compared to those of cis -[Rh2 II, II (μ-DTolF)2 (phen)2 ](BF4 )2 (2 ). Density functional theory (DFT) and electrochemical analyses support the description of the highest occupied molecular orbitals (HOMOs) of3 and4 as possessing contributions from the metals and formamidinate bridging ligands, with Rh2 /form character, and lowest unoccupied molecular orbitals (LUMOs) localized on the respective diimine ligand np and dap π ∗ orbitals. Both3 and4 display strong, low energy Rh2 /form → diimine(π ∗ ) metal/ligand-to-ligand charger transfer ( 1 ML–LCT) transitions with maxima at 566 nm ( ε  = 3600 M −1  cm −1 ) for3 and at 630 nm ( ε  = 2900 M −1  cm −1 ) for4 in CH3 CN. Time dependent-DFT (TD-DFT) calculations support these assignments. The ability of both the bridging np and chelating dap diimine ligands to produce strong absorption of these Rh2 II, II complexes throughout the visible region is potentially useful for the development of new photocatalysts for H2 production and photochemotherapeutics.